Addressing Frequency Control Challenges in Future Low-Inertia Power Systems: A Great Britain Perspective. (August 2021) - Hong, Qiteng; Khan, Md Asif Uddin; Henderson, Callum; Egea-Àlvarez, Agustí; Tzelepis, Dimitrios; Booth, Campbell
Abstract: The ambitious global targets on decarbonization present the need for massive integration of renewable generation in power systems, resulting in a significant decrease in the system inertia. In addition to the reduction in system inertia, the transmission system in Great Britain (GB) faces some unique challenges owing to its relatively small capacity, while being decoupled from other transmission systems and with the renewable resources largely non-uniformly distributed across the system. This paper presents opinions and insights on the challenges associated with frequency control in a low-inertia system and the potential solutions from a GB perspective. In this paper, we focus on three main techniques that act over different time scales: synchronous condensers, inertia emulation, and fast frequency response. We evaluate their relative advantages and limitations with learnings from recent research and development projects in GB, along with the opinions on their roles in addressing the frequency control challenges in future low-inertia systems.